Fractional order based on genetic algorithm PID controller for controlling the speed of DC motors - Ibrahim Khather, Salam; Almaged, Mohammed; I. Abdullah, Abdullah (International Journal of Engineering and Technology, 2019)
Buck boost converter is a good interface between photo voltaic (PV) and the load. It is utilized in applications that require an output voltage of a value above or below the input voltage level. The benefit of using this circuit is to supply a stable and controlled output voltage regardless of the input voltage level. This research presents an optimal design method for fractional-order proportional–integral-derivative (FOPID) controllers of buck boost converter for the purpose of acquiring a group of desired properties. FOPID controller, usually denoted by〖PI^μ D〗^λ, is a special PID controller type in which its derivative and integral orders are fractions between zero and one. Thus, FOPID controller has five variables instead of three in compare with the classical PID controller. In this work, the FOPID is designed to control the speed of Direct Current (DC) motor fed by a buck boost converter. Genetic algorithm will be implemented to set the variables related to the fractional order controller of PID using various type of fitness function such as MSE, ISE and ITSE. The obtained results indicate an enhancement in the steady and transient state performance of system, including the time of settling and rise as well as peak overshoot.